Long-Distance Migrations by Inconnu (Stenodus leucichthys) in the Mackenzie River Syste - Stephenson, S.A.; Burrows, Jeff A.; Babaluk, John A. (ARCTIC, 2010)
Inconnu (Stenodus leucichthys) stocks of the Mackenzie River drainage exhibit complex life histories. In a single stock, some fish may make occasional or regular movements between freshwater and marine environments while others lead a completely freshwater existence. Many inconnu migrate between the Mackenzie River system and the Beaufort Sea, but during spawning migrations, most are believed to move only as far south as the Rampart Rapids near the community of Fort Good Hope. However, an inconnu tagged in the Liard River in northern British Columbia in 2001 was recaptured near Inuvik (Northwest Territories) in 2002, and a second inconnu tagged in the Liard River in 2002 was recaptured near Tuktoyaktuk (Northwest Territories) in 2003. These two fish exhibited some of the longest freshwater migrations by a species from Canadian waters other than Pacific salmon. Otolith strontium distributions of these two fish confirmed migrations of close to 1800 km between fresh and marine waters and indicated different life histories. Additional inconnu tagged in the Liard River in 2002 were recaptured in or near Great Slave Lake in 2002 and 2003. The movements of all these fish suggest that the management of inconnu stocks will be far more complicated than previously thought: they point out the need for management plans and protection that incorporate large geographic areas. Les stocks d’inconnu (Stenodus leucichthys) du bassin du Mackenzie affichent des cycles biologiques complexes. On trouve, au sein d’un seul stock, des poissons qui feront des allers retours sur une base épisodique ou régulière, entre un milieu d’eau douce et un milieu marin, tandis que d’autres passeront toute leur vie en eau douce. Un grand nombre d’inconnus migrent entre le réseau hydrographique du Mackenzie et la mer de Beaufort, mais on pense que, durant les migrations de frai, la plupart ne se déplacent en direction du sud que jusqu’aux rapides Rampart, près de la communauté de Fort Good Hope. Un inconnu marqué dans la rivière Liard dans le nord de ...